The a to Z of French Cinema - Oscherwitz, Dayna; Higgins, MaryEllen (Rowman & Littlefield Publishers, 2009)
It can be argued that cinema was created in France by Louis Lumi_re in 1895 with the invention of the cinZmatographe, the first true motion-picture camera and projector. While there were other cameras and devices invented earlier that were capable of projecting intermittent motion of images, the cinZmatographe was the first device capable of recording and externally projecting images in such a way as to convey motion. Early films such as Lumi_re's La Sortie de l'usine, a minute-long film of workers leaving the Lumi_re factory, captured the imagination of the nation and quickly inspired the likes of Georges MZli_s, Alice Guy, and Charles PathZ. Through the years, French cinema has been responsible for producing some of the world's best directors_Jean Renoir, Jean-Luc Godard, Fran_ois Truffaut, and Louis Malle_and actors_Charles Boyer, Catherine Deneuve, GZrard Depardieu, and Audrey Tautou. The A to Z of French Cinema covers the history of French film from the silent era to the present in a concise and up to date volume detailing the development of French cinema and major theoretical and cultural issues related to it. This is done through a chronology, an introduction, photographs, a bibliography, and hundreds of cross-referenced dictionary entries on many of the major actors, directors, films, movements, producers, and studios associated with French cinema. Going beyond mere biographical information, entries also discuss the impact and significance of each individual, film, movement, or studio included. This detailed, scholarly analysis of the development of film in France is useful to both the novice and the expert alike.